An Urban History of The Plague : Socio-Economic, Political and Medical Impacts in a Scottish Community, 15001650 - Jillings, Karen (London : Taylor and Francis, 2018)
"As a medical, economic, spiritual and demographic crisis, plague affected practically every aspect of an early modern community whether on a local, regional or national scale. Its study therefore affords opportunities for the reassessment of many aspects of the pre-modern world. This book examines the incidence and effects of plague in an early modern Scottish community by analysing bureaucratic, medical and social responses to epidemics in the north-east port of Aberdeen, focusing on the period 1500 to 1650. While Aberdeens experience of plague was in many ways similar to that of other towns throughout Europe, certain idiosyncrasies in the responses articulated within the city make it a particularly interesting case study, which challenges several assumptions about early modern mentalities. "--Provided by publisher.
chapter 1 Setting the scene -- Aberdeen and the north-east / Karen Jillings -- chapter 2 Responses to plague in Scotland / Karen Jillings -- chapter 3 Plague in Aberdeen before 1550 / Karen Jillings -- chapter 4 Plague in Aberdeen after 1550 / Karen Jillings -- chapter 5 Aberdeen$1 (Bs final plague -- s r
Keywords: Cities and towns -- History; History, Modern -- 16th century; History, Modern -- 17th century; History, Modern -- 18th century; British History; Early Modern History 1500-1750; Urban History; Great Britain -- History